A Review of the Therapeutic Benefits of Moringa oleifera in Controlling High Blood Pressure (Hypertension) - Okorie, Chuku; Ajibesin, Kola; Sanyaolu, Adekunle; Islam, Adeena; Lamech, Selciya; Mupepi, Kudakwashe; Mupepi, Tatenda; Oseni, Akeem; Oyeleke, Oluwayemisi; Abioye, Amos (Current Traditional Medicine, 2019)
Moringa oleifera (M. oleifera) is an angiosperm plant that is a member of the Moringaceae family. It is a natural plant that is native to the sub-Himalayan northern regions of India, Bangladesh, Pakistan, and Afghanistan. The plant grows abundantly throughout tropical and subtropical areas of the world. For several centuries, many cultures have utilized various parts of the moringa plant as traditional medicine to treat common illnesses and control life-threatening conditions such as hypertension (HTN), diabetes, hyperlipidemia, inflammation, etc. This article reviewed the current literature on the therapeutic benefits of M. oleifera on hypertension, primarily focusing on identifying the plant’s key components and its roles in hindering the common pathophysiological pathways associated with hypertension. The number of people living with HTN has been predicted to increase to 1.56 billion worldwide by 2025 in spite of the myriads of preventive and treatment strategies available today. Therefore, it would be of great value to explore alternative complementary ways of controlling high blood pressure. HTN is commonly defined as blood pressure equal to or higher than 140/90 mm Hg. HTN itself is not a disease condition and does not elicit specific symptoms, however, if left untreated for a long time, it can lead to complicated cardiovascular diseases such as angina, congestive heart failure, myocardial infarction as well as stroke and chronic kidney diseases. Primary hypertension is diagnosed when there is no known identifiable underlying cause for the onset of the condition. Secondary hypertension is diagnosed when there is evidence of a disease or disorder triggering the onset of the condition. It is apparent that understanding the role of M. oleifera in the management of hypertension would expand the valuable strategies for the control of this condition.
Keywords: antihypertensive